Addressing Adolescents’ Depressive Symptoms and Risky Behavior: The Role of Perceived Parents’ and Teachers’ Social Support - Rubach, Charlott; Dicke, Anna-Lena; Lazarides, Rebecca; Simpkins, Sandra; Eccles, Jacquelynne S. (Journal of Organizational Psychology, 2020)
Socializer-driven processes were analyzed by investigating effects of perceived mothers’, fathers’, and teachers’ social support on adolescents’ depressive symptoms and risky behavior across each academic year in high school. Furthermore, we analyzed the co-development of parents’ and teachers’ social support and adolescents’ depressive symptoms and risky behavior using data from 402 adolescents from the Childhood and Beyond Study. Perceived mothers’ social support protected adolescents from depressive symptoms from 9th to 11th grade. Gender-specific associations were identified. Teachers’ social support predicted declines in depressive symptoms only for females. Perceived fathers’ social support predicted an increase in depressive symptoms for their sons only.